Rigidity guided localisation for mobile robotic sensor networks. (2nd August 2010) - Wu, Changhua; Zhang, Ying; Sheng, Weihua; Kanchi, Saroja
This paper introduces a rigidity-guided localisation approach for mobile robotic sensor networks. The localisation uses a distance graph composed of both the robot-to-robot ranging data and the motion trajectories from robot odometry. The motion of a robot depends on the result of the rigidity test of its local distance graph: if the graph is not uniquely localisable, the robot moves around in its neighbourhood to collect at least two extra ranging data with each of its neighbours in order to make the extended graph uniquely localisable. Locally unique maps are then merged into a globally consistent map.